Dynamics of the tuning process between singers - Urteaga, Raul (2004)
We present a dynamical model describing a predictable human behavior like the tuning process between singers. The purpose, inspired in physiological and behavioral grounds of human beings, is sensitive to all Fourier spectrum of each sound emitted and it contemplates an asymmetric coupling between individuals. We have recorded several tuning exercises and we have confronted the experimental evidence with the results of the model finding a very well agreement between calculated and experimental sonograms.